A population of small refractory meteoroids in asteroidal orbits. (1st December 2015) - Campbell-Brown, M.
Abstract: More than 7000 two-station meteors observed with two different video systems, both parts of the Canadian Automated Meteor Observatory, have been analysed. The more sensitive (limiting magnitude +6.5) influx system shows a significant population of slow meteors with begin heights under 86 km, while the less sensitive (limiting magnitude +4) tracking system shows many more fast meteors ablating at high altitudes. The low, slow population has asteroidal orbits with low inclinations and moderate eccentricities, and radiants which are not, in general, associated with the sporadic sources. In spite of their low begin heights, which imply that they are strong and refractory, the meteors have early peaked light curves which are not predicted by classical ablation theory for non-fragmenting objects. Abstract : Highlights: More than 7000 two station meteors from two camera systems have been analysed. The more sensitive system shows more slow meteors with low begin heights. These low meteors have asteroidal orbits and are outside the sporadic sources. The meteors have sudden onset lightcurves inconsistent with classical ablation theory.